2000
DOI: 10.1007/s000110050581
|View full text |Cite
|
Sign up to set email alerts
|

Distinct ability to accumulate eosinophils during the inflammatory cellular response to M. Bovis BCG in the mouse pleural cavity

Abstract: Mycobacterial load and mouse susceptibility seem to determine the early granulocyte dynamics in the lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Mycobacterial infections frequently show eosinophil recruitment in both naturally occurring infections in human patients (11,26) and in animal experimental infections (6,14,17,20,27). Enhanced eosinophil recruitment to sites of infection has been associated with unrestricted growth of mycobacteria observed in mouse susceptible strains in contrast to resistant ones (27) and in mice deficient in gamma interferon (IFN-␥ Ϫ/Ϫ ) that are highly susceptible to infection with tuberculosis-causing organisms (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mycobacterial infections frequently show eosinophil recruitment in both naturally occurring infections in human patients (11,26) and in animal experimental infections (6,14,17,20,27). Enhanced eosinophil recruitment to sites of infection has been associated with unrestricted growth of mycobacteria observed in mouse susceptible strains in contrast to resistant ones (27) and in mice deficient in gamma interferon (IFN-␥ Ϫ/Ϫ ) that are highly susceptible to infection with tuberculosis-causing organisms (13).…”
mentioning
confidence: 99%
“…Enhanced eosinophil recruitment to sites of infection has been associated with unrestricted growth of mycobacteria observed in mouse susceptible strains in contrast to resistant ones (27) and in mice deficient in gamma interferon (IFN-␥ Ϫ/Ϫ ) that are highly susceptible to infection with tuberculosis-causing organisms (13). Moreover, eosinophilia has been associated with higher rates of active tuberculosis in human immunodeficiency virus type 1-infected adults (9), suggesting that eosinophils may have roles in pathogenesis and susceptibility to mycobacterial infection.…”
mentioning
confidence: 99%
“…This was accompanied by a large accumulation of eosinophils during the inflammatory cell reaction to M. Bocis M. Bovis in the pleural cavity of the mouse than to other known eosinophilia inducers: IL-5, PAF-acether. Mycobacterial and mouse susceptibility determine the early dynamics of changes in granulocytes [6].…”
Section: амурский медицинский журнал №3 (19) 2017mentioning
confidence: 99%
“…This was accompanied by a large accumulation of eosinophils during the inflammatory cell reaction to M. Bocis M. Bovis in the pleural cavity of the mouse than to other known eosinophilia inducers: IL-5, PAF-acether. Mycobacterial and mouse susceptibility determine the early dynamics of changes in granulocytes [6].Aluminum lactate, introduced to experimental rats, produced skeletal necrosis of the muscle of the diaphragm and abdominal wall. Ultrastructural studies of the diaphragm showed inoculation covering the collagen fibers that connect near the basal plate of the muscle, and limited within the phagocytes [2].…”
mentioning
confidence: 99%
“…Pleural mesothelial cells are able to initiate and regulate an innate response to Mycobacterium species infection by stimulating cytokine production as well as cell accumulation in the pleural cavity (12,18,19,21). Accumulation of inflammatory cells and T lymphocytes in pleural exudate is often observed as much in patients with tuberculous pleurisy (14) as in experimental infection (17,20,23,30). It is also known that pleural effusion derived from mycobacterial infection presents high numbers of type 1 cytokine producer lymphocytes in pleural fluid (13).…”
mentioning
confidence: 99%